2021
DOI: 10.3390/horticulturae7020033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Root Rot Disease in Agricultural Crops

Abstract: Root rot diseases remain a major global threat to the productivity of agricultural crops. They are usually caused by more than one type of pathogen and are thus often referred to as a root rot complex. Fungal and oomycete species are the predominant participants in the complex, while bacteria and viruses are also known to cause root rot. Incorporating genetic resistance in cultivated crops is considered the most efficient and sustainable solution to counter root rot, however, resistance is often quantitative i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 356 publications
1
38
0
1
Order By: Relevance
“…Autotoxins and pathogens accumulated in the soil aggravate root rot diseases ( 4 , 11 ). Previous studies have shown that some autotoxins inhibit the performance of the plant species that produce them and promote the growth and pathogenicity of soilborne pathogens ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autotoxins and pathogens accumulated in the soil aggravate root rot diseases ( 4 , 11 ). Previous studies have shown that some autotoxins inhibit the performance of the plant species that produce them and promote the growth and pathogenicity of soilborne pathogens ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of root rot include soft, water-soaked, dark brown to black lesions on the roots, yellow color and wilting of leaves, causing stunted plant growth and reduced yield. Cultural, physical, biological, and chemical control methods have been used as management strategies to control root rot diseases ( 4 ). However, these control methods have only been partially successful because the pathogens and other factors are complicated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the R. solani is a facultative parasite and can easily compete with other soil born saprophytes. In order to survive in the soil, it develops sclerotia, a long-lasting structures or propagules ( Williamson-Benavides and Dhingra, 2021 ). These nutrient-independent propagules are formed from the undifferentiated hyphae or monilioid cells.…”
Section: Fungal and Oomycetes Pathogensmentioning
confidence: 99%
“…Four important Pythium spp. such as P. ultimum , P. irregulare , P. aphanidermatum , and P. myriotylum have been reported from alfalfa fields and are the most common root rot causing pathogens in the world ( Williamson-Benavides and Dhingra, 2021 ). During 2017 and 2019, 30 to 80% of alfalfa plants in Gansu province stunted, wilted, and dried.…”
Section: Fungal and Oomycetes Pathogensmentioning
confidence: 99%
“…Indeed, Ag NPs can be helpful in plant disease control against pathogenic fungi [14]. In a recent study, the effect of Ag NPs on R. solani groups that contaminate cotton plants was assessed [15]. Ag NPs generate reactive oxygen species (ROS), especially superoxide radicals (O −2 ) and hydroxyl radicals (OH), that destroy the cell [16].…”
Section: Introductionmentioning
confidence: 99%